Pengaruh Subsidi Harga Pada Keputusan Pembelian di Tiktok Shop (Studi kasus pada Mahasiswi Perguruan Tinggi): The Effect of Price Subsidies on Purchasing Decisions on Tiktok Shop (case study on College Students) - Putri Sintawati (Asosiasi Ahli Administrasi Indonesia, 2023)
The aim of this research is to determine and analyze the effect of price subsidies on purchasing decisions at Tiktokshop among college students in the city of Bandung, Indonesia. Using quantitative descriptive research methods, the sample used in this research consisted of 102 respondents who were university students in the city of Bandung who were active in distributing questionnaires. Next, data analysis uses descriptive, correlation and regression. The results of the research obtained information that price subsidies had a low influence on the purchasing decisions of Bandung city university students when purchasing at Tiktokshop.